Development of the Professional Learning Community Management Model to Promote Proactive Learning Management Aimed at Improving the Academic Achievement of Students at Wat Pak Dong Tha San School - Boonpraseard, Piroad (Journal of Dhamma for Life, 2026)
This research had the research objectives to 1) Study the components of professional learning communities, components of teachers' active learning management, professional learning community guidelines, and guidelines for promoting teachers' active learning management. 2) Create and verify the quality of a professional learning community model to promote teachers' active learning management abilities to improve the academic achievement of students at Wat Pak Dong Tha San School. 3) Study the results of using the professional learning community model to promote teachers' active learning management abilities towards improving the academic achievement of students at Wat Pak Dong Tha San School and 4) Study the satisfaction of the professional learning community model to promote teachers' active learning management ability towards improving the academic achievement of students at Wat Pak Dong Tha San School. The sample group consisted of 10 teachers from Wat Pak Dong Tha San School, Suphan Buri Primary Educational Service Area Office 3, 52 students in grades 4-6, and 97 parents of students in grades 1-6. The research instruments used were questionnaires, interviews, and tests. Data analysis was performed using percentage, mean, standard deviation (S.D.) and content analysis.